The use of force by the states under international law - Alqahtani, Mohammed Salem; Rohaida Nordin; Faridah Jalil (Penerbit Universiti Kebangsaan Malaysia, 2021)
Notwithstanding the strict restriction on the use of military force under Article 2(4) of the United Nations Charter (UN Charter), notable exceptions to the provision are conferred in Article 51. There are various interpretations among the states and researchers on Article 51 of the UN Charter. Consequently, some questions beg for answers and will: what makes up an ‘armed attack’ and what does ‘occurs’ mean? Does it mean that States should wait until they have been attacked before defending themselves? Can states rely on Article 51 of the Charter to use military force on terrorist group(s) in the name of self-defense? Is there any time limit within which the state can defend itself in self-defense? What is collective security? Thus, this research is undertaken to examine and provide answers to the above said questions by using a doctrinal legal research methodology. The findings reveal that Article 2(4) of the UN Charter encompasses the actual use of armed force and the threat to use force. The use of force through irregular forces should be regarded as an armed attack by the Charter; and a state’s right to defend itself is not without limitation or time limit. The UN Charter has not defined ‘armed attack’. Therefore, the authors recommend for the UN Charter amendment to provide a clause that will extend the meaning of ‘armed attack’ to include not only acts by regular forces but also irregular forces.